Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1039/c7ta02268a
|View full text |Cite
|
Sign up to set email alerts
|

One-step extended strategy for the ionic liquid-assisted synthesis of Ni3S4–MoS2heterojunction electrodes for supercapacitors

Abstract: A Ni3S4–MoS2 heterojunction was successfully prepared with the assistance of an ionic liquid in one step, and it showed high performance as a supercapacitor electrode. This synthesis strategy can be applied to prepare other MxSy–MoS2 heterojunctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 41 publications
3
46
0
1
Order By: Relevance
“…First, BMIMSCN can change the reaction path and regulate the reaction rate. As reported by previous study, the BMIMSCN can react with (NH 4 ) 6 Mo 7 O 24 ·4H 2 O to form a rod‐like precursor that composed of [BMIM] 2 Mo 4 O 13 . In our study, when the Ni 2+ and (NH 4 ) 6 Mo 7 O 24 ·4H 2 O added into the solvent of deionized water and BMIMSCN, Ni 2+ may preferentially reacted with SCN − to form NiS, while Mo 7 O 24 6− reacted with BMIM + to form the Mo precursor.…”
Section: Resultssupporting
confidence: 78%
“…First, BMIMSCN can change the reaction path and regulate the reaction rate. As reported by previous study, the BMIMSCN can react with (NH 4 ) 6 Mo 7 O 24 ·4H 2 O to form a rod‐like precursor that composed of [BMIM] 2 Mo 4 O 13 . In our study, when the Ni 2+ and (NH 4 ) 6 Mo 7 O 24 ·4H 2 O added into the solvent of deionized water and BMIMSCN, Ni 2+ may preferentially reacted with SCN − to form NiS, while Mo 7 O 24 6− reacted with BMIM + to form the Mo precursor.…”
Section: Resultssupporting
confidence: 78%
“…It has been observed that these devices show a capacity of 985.21 F g −1 at a current density of 1 A g −1 , and it goes down to 573 F g −1 after 20 000 cycles at a current density of 10 A g −1 . Further, with activated carbon electrodes these demonstrated a high energy density of 58.43 W h kg −1 and power density of 385.95 W kg −1 . The core–shells of the NiCo 2 S 4 @ MoS 2 type having the structures of dodecahedrons have been prepared from zeolitic imidazolate frameworks as templates.…”
Section: Applications Of Mos2 For Energy Conversion and Storagementioning
confidence: 99%
“…[57] This outstanding ionic conductivity could be closely associatedw ith the well-designed heterostructures. [23,58] To further analyze the possible lithium storagem echanism for the FeS 2 /MoS 2 electrode during the lithiation andd elithiation processes, ex-situ XRD, HRTEM, and EXAFS were performed. Figures 5a,b [19,59] whereas the MoS 2 phase disappears and Li x MoS 2 with poor crystallinity may be formed as ar esulto ft he lithiation process of MoS 2 (MoS 2 + x Li + + x e À !Li x MoS 2 ).…”
Section: Introductionmentioning
confidence: 99%